KEMANDIRIAN DAN MOTIVASI BERPRESTASI SISWA MADRASAH ALIYAH SUNAN PANDANARAN SLEMAN - Arif Saeful Anwar; Berliana Henu Cahyani (JURNAL SPIRITS, 2012)
ABSTRACTThis study is intended to find out the relationship between adolescent tonomy and achievement motivation. The subjects of study are studentsr Sunan Pandanaran senior high school, Sleman, Yogyakarta. The amount r the students are 78 (seventy eight) students. In this study, researcher Fed correlation studies of Product-Momen Pearson. The researcher Fed purposive sampling to collect the data. Then, the researcher process ata used a scale of achievement motivation and authonimy. The scale of chievement motivation consists of 35 items and the scale of authonomy onsists of 41 items.The results of this study showed that there is a correlation coefficient in the amount for significance level, it is 0.645, and 0.000 (p <0.05). It means zat hyphotesis explained that the positive relationship between achievement iotivation and authonomy can be accepted The effectiveness of regression n the study is 41.6%, it means that 14.4% achievement motivation is etermined by authonomy and 57.4% is influenced by other factors. Such rs natural factors; birth order, gender, age, and environmental factors as ike; parent's education, culture, education and occupation.Key words: Autonomy, achievement motivation